2012
DOI: 10.1097/opx.0b013e318255da45
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Analysis of U.S. Contact Lens User Demographics

Abstract: Four demographic variables, age, socioeconomic status, age-gender interaction, and socioeconomic status-education interaction, defined those likely to be using contact lens on any given day in the United States. Together, these four variables identify almost 9 of 10 contact lens users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 7 publications
3
22
0
Order By: Relevance
“…The observed groups reflected the male/female mix of SCL wearers in the United States with one-third male wearers 39 ; HydDD wearers were 31.2% male and SiHyDD wearers were 33.4% male (P ¼ 0.42). The HydDD cohort was statistically significantly younger compared to the SiHyDD cohort (mean 30.3 6 12.9 years versus 33.2 6 13.9 years, respectively, P ¼ 0.0002, Fig.…”
Section: Observed Cohortsmentioning
confidence: 97%
“…The observed groups reflected the male/female mix of SCL wearers in the United States with one-third male wearers 39 ; HydDD wearers were 31.2% male and SiHyDD wearers were 33.4% male (P ¼ 0.42). The HydDD cohort was statistically significantly younger compared to the SiHyDD cohort (mean 30.3 6 12.9 years versus 33.2 6 13.9 years, respectively, P ¼ 0.0002, Fig.…”
Section: Observed Cohortsmentioning
confidence: 97%
“…Today, soft contact lenses are the most widely used type of contact lens, with an estimated 125 million wearers worldwide and over 30 million in the United States . Recent research suggests that the peripheral optical properties of a lens, whether a spectacle or contact lens, may influence the progression of myopic refractive error in animals and humans .…”
mentioning
confidence: 99%
“…4 Today, soft contact lenses are the most widely used type of contact lens, with an estimated 125 million wearers worldwide 5 and over 30 million in the United States. 6,7 Recent research suggests that the peripheral optical properties of a lens, whether a spectacle or contact lens, may influence the progression of myopic refractive error in animals 8,9 and humans. 10,11 Many of these studies have identified a stabilisation of axial length with these optics and soft contact lenses have emerged as a promising treatment option for slowing the progression of myopia A number of human clinical trials on control of myopia have been conducted in Asia, where the prevalence and penetration of myopia (and high myopia) are greater than in North America.…”
mentioning
confidence: 99%
“…Contact lenses are optical devices regulated by the US Food and Drug Administration (FDA) . Approximately 140 million people worldwide and 40.9 million people in the US use contact lenses to correct refractive errors in myopia, hyperopia, and astigmatism cases . The contact lens global market is predicted to reach over 19 billion US dollars by 2024 .…”
Section: Introductionmentioning
confidence: 99%